The two alternative NADH: quinone oxidoreductases from Staphylococcus aureus - Sena, Filipa V. (2024)
Staphylococcus aureus is an opportunistic pathogen that has emerged as a major public health threat due to the increased incidence of its drug resistance. S. aureus presents a remarkable capacity to adapt to differentniches due to the plasticity of its energy metabolism. In this work, we investigated the energy metabolism of S. aureus, focusing on the alternative NADH:quinone oxidoreductases, NDH-2s. S. aureus presents two genes encoding NDH-2s (NDH-2A and NDH-2B) and lacks genes coding for Complex I, the canonical respiratory NADH:quinone oxidoreductase. This observation makes the action of NDH-2s crucial for the regeneration of NAD+ and, consequently, for the progression of metabolism. Our study involved the comprehensive biochemical characterization of NDH-2B and the exploration of the cellular roles of NDH-2A and NDH-2B, utilizing knockout mutants (Δndh-2a and Δndh-2b). We show that NDH-2B uses NADPH instead of NADH, does not establish a charge-transfer complex in the presence of NADPH, and its reduction by this substrate is the catalytic rate-limiting step. In the case of NDH-2B, the reduction of the flavinis inherently slow, and we suggest the establishment of a charge transfer complex between NADP+ and FADH2, as previously observed for NDH-2A, to slow down quinone reduction and, consequently, prevent the overproduction of reactive oxygen species, which is potentially unnecessary. Furthermore, we observed that the lack of NDH-2A or NDH-2B impacts cell growth, volume, and division differently.The absence of these enzymes results in distinct metabolic phenotypes, emphasizing the unique cellular roles of each NDH-2 in energy metabolism.